Case Report: Suboptimal response to standard-dose asfotase alfa in perinatal hypophosphatasia indicates a need for individualized dosing - Petković Ramadža, Danijela; Žigman, Tamara; Čavka, Mislav; Barić, Ivo (Frontiers in Endocrinology, 2025)
Hypophosphatasia (HPP) is a rare, inherited metabolic disorder due to a deficiency of tissue-nonspecific alkaline phosphatase, characterized by defective bone and teeth mineralization with consequent problems, including respiratory failure in severe types of HPP. Severe patients exhibit other disease-related manifestations, including neurological manifestations, which make HPP complex and difficult to manage. Enzyme replacement therapy with asfotase alfa is a disease-specific treatment for skeletal manifestations in pediatric patients. We present a patient with perinatal HPP who had a severe clinical course with respiratory insufficiency during infancy requiring a higher dose of asfotase alfa than recommended (12 mg/kg/week). After improvement of respiratory function and outgrowing the higher dose, the patient was maintained on the standard dose (6 mg/kg/week) from the age of 3 years. At 6 years of age, unexplained clinical and radiographic deterioration occurred while laboratory parameters remained normal. Following a traumatic humerus fracture that occurred after several months, asfotase alfa was increased to 10 mg/kg/week. Remarkable clinical improvement was observed and the patient regained the ability to walk unassisted 3 months after the dose correction. The rickets severity score changed from 10 to 3.5 within 14 months. No side effects from the higher drug dose have been noticed. The remaining challenge in this patient was a neurodevelopmental disorder. In conclusion, the standard dose of asfotase alfa was not sufficient to treat the skeletal manifestations of HPP in our patient, indicating that some perinatal HPP patients should be treated with higher doses to reach treatment goals. Although bone disease and patient outcomes have been improved with tailored drug doses, neurological manifestations of HPP remain challenging.